How to find $$\sum_{k \text{ odd}} \frac{2(k^2-1)}{k^4+k^2+1}$$ Here we find $\displaystyle\sum_{k=1}^{\infty} \frac{2(k^2-1)}{k^4+k^2+1}=1$ and we know that $\displaystyle\sum_{k \,\text{odd}} + \sum_{k \,\text{even}}=1.$ Can we use this information to find sum? Or, maybe we can find it on other way?

We can say that our sum is equal to $$\color{red}{2}\sum_{k=1}^{\infty}\frac{(2k-1)^2-1}{(2k-1)^4+(2k-1)^2+1}=\sum_{k=1}^{\infty} \left(\frac{1-4k}{4k^2-2k+1}+\frac{4k-3}{4k^2-6k+3}\right),$$ but I don't think we can see something from that.

EDIT: Actually, Wolfram find that $$2\sum_{k=1}^{\infty}\frac{(2k-1)^2-1}{(2k-1)^4+(2k-1)^2+1}=\pi \text{sech}\left(\frac{\sqrt{3} \pi}{2}\right).$$ It's pretty nice closed form.


I write here so everyone can see. I finally solve it.

First, note that $$\sum_{k \text{ odd}} \frac{2(k^2-1)}{k^4+k^2+1}=\sum_{k=1}^{\infty}(-1)^{k-1}\frac{2k-1}{k^2-k+1},$$ because $$\sum_{k=1}^{\infty}(-1)^{k-1}\frac{2k-1}{k^2-k+1}=\sum_{k\, \text{odd}}\left(\frac{2k-1}{k^2-k+1}-\frac{2(k+1)-1}{(k+1)^2-(k+1)+1}\right).$$

Now, use formula $$\frac{1}{\cos \pi z}=\frac{4}{\pi}\sum_{k=0}^{\infty} (-1)^k \frac{2k+1}{(2k+1)^2-(2z)^2}=\frac{4}{\pi}\sum_{k=1}^{\infty} (-1)^{k-1} \frac{2k-1}{(2k-1)^2-(2z)^2}$$ and set $z=i\cdot \alpha.$ We find $$\text{sech}(\pi \alpha)=\frac{4}{\pi}\sum_{k=1}^{\infty}(-1)^{k-1}\frac{2k-1}{(2k-1)^2+4\alpha^2}$$ and then setting $\displaystyle\alpha = \frac{\sqrt{3}}{2}$ we find $$\text{sech}\left(\frac{\sqrt{3}\pi}{2}\right)=\frac{4}{\pi}\sum_{k=1}^{\infty}(-1)^{k-1}\frac{2k-1}{(2k-1)^2+3}=\frac{1}{\pi}\sum_{k=1}^{\infty}(-1)^{k-1}\frac{2k-1}{k^2-k+1}$$ or $$\sum_{k \text{ odd}} \frac{2(k^2-1)}{k^4+k^2+1}=\sum_{k=1}^{\infty}(-1)^{k-1}\frac{2k-1}{k^2-k+1}=\pi \text{sech}\left(\frac{\sqrt{3}\pi}{2}\right).$$

Added: Formula $$\frac{1}{\cos \pi z}=\frac{4}{\pi}\sum_{k=0}^{\infty} (-1)^k \frac{2k+1}{(2k+1)^2-(2z)^2}$$ is derived from (same link as above) $$\pi \tan \pi z = \sum_{k=0}^{\infty} \frac{8z}{(2k+1)^2 - 4z^2}, \qquad (2z \neq \pm 1, \pm 3, \dots).$$ From $\dfrac{1}{\sin z}=\cos z + \tan \dfrac{z}{2}$ we find, further, that $$\frac{\pi}{\sin \pi z}=\frac{1}{z}-\frac{2z}{z^2-1^2}+\frac{2z}{z^2-2^2}\pm\cdots, \qquad (z \neq 0, \pm 1, \pm 2, \dots),$$ and finally, replacing $z$ here by $\dfrac{1}{2}-z,$ $$\frac{\pi}{4 \cos \pi z}=\frac{1}{1^2-(2z)^2}-\frac{3}{3^2-(2z)^2}+\frac{5}{5^2-(2z)^3}\pm \cdots, \qquad (2z \neq \pm 1, \pm 3, \dots).$$

  • $\begingroup$ Just beautiful! (+1) $\endgroup$ – user 1591719 Feb 20 '13 at 21:22
  • $\begingroup$ Thanks. I have to admit that I cheated a bit, because I start from Wolfram solution and then find answer. $\endgroup$ – Cortizol Feb 20 '13 at 21:27
  • $\begingroup$ It doesn't matter. The solution is very clever. $\endgroup$ – user 1591719 Feb 20 '13 at 21:27

Maple gets $${\frac {2}{229}}\,\sum _{r={\it RootOf} \left( 16\,{{\it \_Z}}^{4}-32 \,{{\it \_Z}}^{3}+24\,{{\it \_Z}}^{2}-6\,{\it \_Z}+1 \right) } \left( 56\,{r}^{3}-45\,{r}^{2}-23\,r+21 \right) \Psi \left( 1-r \right)$$

The quartic is irreducible with two pairs of complex-conjugate roots. I don't know if there's any reason to expect the values of $\Psi(1-r)$ to have any special relations (other than $\overline{\Psi(1-r)} = \Psi(1-\overline{r})$).

  • $\begingroup$ I don't know if there is nice solution. It's interesting that if we , for example, put that sum start from $k=1$ Wolfram can't find closed form, but if we set $k=0$ Wolfram find nice closed form. I'm talking about wolframalpha.com/input/… and wolframalpha.com/input/… $\endgroup$ – Cortizol Feb 19 '13 at 19:56
  • $\begingroup$ for which sum Maple gets that result? $\endgroup$ – Cortizol Feb 20 '13 at 20:14

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.